The vulnerability of Bajau Laut as stateless people in Sabah - Wan Shawaluddin Wan Hassan; Diana Peters (Penerbit UMS, 2020)
The Bajau Laut or Sea Bajau or also often referred to with the derogatory label Palauh by other communities, are known to be living within their ancestral domain of the Sulu and the Celebes Seas or the Sulu-Semporna-South Sulawesi Triangle. During the pre-British period, their mobility around this region was well established as part of their civilization and was not an issue with other peoples in the land-based territories. However, the legal status of the Bajau Laut became problematic when citizenship and territories were formalized by the emergence of the nation-states of the Philippines, Malaysia and Indonesia. In the case of the Bajau Laut population located on the Malaysian side of Sabah, the dynamics of their own internal development has become more complicated. In Sabah, there are three groups of Bajau: The West Coast Bajau, the various groups of East Coast Bajau and the Bajau Laut who can be found along Sabah’s east coast, and around the islands off of Semporna. These three groups can be differentiated by their language and dialects, as well as livelihood, status in life, education, community structure and their general worldviews. The West Coast Bajau and the East Coast Bajau have slowly integrated themselves into the Malaysian society, while the Bajau Laut continues their seminomadic life at sea and are generally regarded as stateless by the Malaysian Government. This paper looks into the changes that has occurred within the Bajau Laut group and how they are viewed by the Sabah government and society. One of the main finding of this paper is that the status of the Bajau Laut as stateless has made them more vulnerable and easily exploited. This in turn presents as a possible security problem to the state as these people pledges allegiance to no one.